2020
DOI: 10.1155/2020/5783107
|View full text |Cite
|
Sign up to set email alerts
|

The Utility of Psoas Muscle Assessment in Predicting Frailty in Patients Undergoing Transcatheter Aortic Valve Replacement

Abstract: Background. The rise in an ageing population has resulted in an increase in the prevalence of aortic stenosis. With the advent and rapid expansion in the use of transcatheter aortic valve replacements (TAVRs), patients with severe aortic stenosis, traditionally thought too high risk for surgical intervention, are now being treated with generally favourable results. Frailty is an important factor in determining outcome after a TAVR, and an assessment of frailty is fundamental in the identification of appropriat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Among older adults without HIV, lower psoas quality and/or quantity have been associated with frailty and falls. [49][50][51] We have previously shown greater odds of lower functional status associated with the immune activation biomarker CD8 + CD38/HLA-DR and increased levels of IL-6 in PWH. 46 In addition, we have found that higher density (less fat) psoas and paraspinal muscle were associated with better physical function.…”
Section: Discussionmentioning
confidence: 99%
“…Among older adults without HIV, lower psoas quality and/or quantity have been associated with frailty and falls. [49][50][51] We have previously shown greater odds of lower functional status associated with the immune activation biomarker CD8 + CD38/HLA-DR and increased levels of IL-6 in PWH. 46 In addition, we have found that higher density (less fat) psoas and paraspinal muscle were associated with better physical function.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have shown that radiologically assessed PMA, as a surrogate of sarcopenia, was related to surgical mortality in various surgical settings, such as transcatheter aortic valve implantation [ 6 ], abdominal [ 7 ], and femur fracture surgery [ 5 , 22 ]. Based on these results, we considered the underlying relationship between surgical mortality and low PMA.…”
Section: Discussionmentioning
confidence: 99%
“…PMA normalization is necessary to consider its clinical use because it differs according to race, sex, and age. Several PMA normalization methods have been used, such as the psoas: L4 vertebrae index [ 5 , 6 ], which is normalized by BMI, BSA [ 12 ], and height [ 7 ]. Some studies using CT-measured PMA used height 2 for adjustment; the present study utilized BSA, according to Canales et al [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we used the Edmonton Frail Scale (EFS) as a second and multi-domain instrument to assess frailty ( Supplementary Table S4 ) [31] . Rolfson et al demonstrated that the EFS is a valid tool for determining frailty when compared to the CGA and the EFS is used in several cardiac populations, including heart failure patients, in literature [32] , [33] , [34] , [35] .…”
Section: Methodsmentioning
confidence: 99%